The Transformation of the Leadership of the Santi Asromo Majalengka Islamic Boarding School: From Personal Authority to Impersonal - Syamsuddin Syamsuddin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This article aims to analyze the transformation of the kyai's leadership at Pesantren Santi Asromo Majalengka. The research is focused on exploring the leadership system, the factors causing the shift in the style of leadership, and the authority of the kyai in the organizational structure of the pesantren. The research was conducted using a qualitative approach through the descriptive analysis method. The research data were collected through observation, interviews and documentation. The results of the study concluded that the leadership system of the Santi Asromo pesantren transformed personal to impersonal, from paternalistic to bureaucratic, from a single authority to a collective. The pesantren leadership system is based on a prototype of lifelong leadership and a kinship system. The shift in leadership styles can be categorized into two periods, namely the leadership period of Kyai Abdul Halim and Kyai Abdul Qohar who tend to be charismatic, and the leadership of Kyai Amas Turmudzi who tends to be rational. The authority of the kyai in the organizational structure of the pesantren has changed along with changes in social society, the education system, and the legalization of the role of the family.Artikel ini bertujuan untuk menganalisis transformasi kepemimpinan kyai di Pesantren Santi Asromo Majalengka. Penelitian difokuskan menggali sistem kepemimpinan, faktor penyebab pergeseran dan otoritas kyai dalam struktur organisasi pesantren. Penelitian dilakukan dengan menggunakan pendekatan kaulitatif melalui metode analisis deskriptif. Data penelitian dikumpulkan melalui observasi, wawancara dan dokumentasi. Hasil penelitian menyimpulkan sistem kepemimpinan pesantren mengalami transformasi dari yang bersifat personal menjadi impersonal, dari paternalistik menjadi birokratik, dari otoritas tunggal menjadi kolektif. Sistem kepemimpinan pesantren didasarkan pada prototipe kepemimpinan seumur hidup dan sistem kekerabatan. Pergeseran corak kepemimpinan dapat dikategorisasikan ke dalam dua periode, yakni kepemimpinan Kyai Abdul Halim dan Kyai Abdul Qohar yang cenderung kharismatik dan kepemimpinan Kyai Amas Turmudzi yang cenderung rasional. Otoritas kyai dalam struktur organisasi berubah disebabkan perubahan sosial, sistem pendidikan dan legalisasi peranan keluarga.